Investigation of Etching Process in Nano Structures - Andriukaitis, D.; Anilionis, R. (Elektronika ir Elektrotechnika, 2008)
Problems of etching process, related with MOS transistors separation in SOS technologys was researched. Wet Etching provide a higher degree of selectivity than dry etching techniques. In isotropic etching materials are removed uniformly from all directions. A vertical profile can be easily made using anisotropic etching and it solves the problem of lateral etching. Using dry etching it is much easier to start and stop than simple immersion wet etching and less lateral encroachment is achieved. The main avantage of ion milling is directionality. That’s why less lateral encroachment during region formation could be achieved using ion milling according to wet and dry etching process simulation results. Ill. 8, bibl. 6 (in English; summaries in English, Russian and Lithuanian).